2015
DOI: 10.19030/iber.v14i6.9508
|View full text |Cite
|
Sign up to set email alerts
|

Does Education Pay In South Africa? Estimating Returns To Education Using Two Stage Least Squares Approach

Abstract: This paper investigates, using the first three waves of the National Income Dynamic dataset, the link between education and wages. Specifically it estimates the potential impact of the educational levels on wages in South Africa over the period 2008 – 2012.  A two-stage least squares (2SLS) method is applied to account for endogeneity bias. More specifically, we use a lagged education as an instrumental variable in a two-stage least squares framework. Our results show that the proposed instruments is relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Crespo Cuaresma and Raggl (2016) demonstrated that the return to schooling was more than 5 percent in Uganda. Biyase and Zwane (2015) used the fixed effects model and found that the return to education was 2.2 percent in South Africa. Peet et al (2015) used 61 nationally representative household surveys from 25 developing countries between 1985 and 2012, and showed that the return to education in developing countries was 7.5 percent.…”
Section: Previous Studies Regarding Returns To Educationmentioning
confidence: 99%
“…Crespo Cuaresma and Raggl (2016) demonstrated that the return to schooling was more than 5 percent in Uganda. Biyase and Zwane (2015) used the fixed effects model and found that the return to education was 2.2 percent in South Africa. Peet et al (2015) used 61 nationally representative household surveys from 25 developing countries between 1985 and 2012, and showed that the return to education in developing countries was 7.5 percent.…”
Section: Previous Studies Regarding Returns To Educationmentioning
confidence: 99%
“…We addressed the endogeneity issue by running a two-stage least squares regression. Given the challenges of finding a valid instrumental variable, we followed Gregorio and Lee (2002) and Biyase and Zwane (2015), who used the lagged value of education as an instrument in their studies. We employed the education levels during the past two years as our instrumental variables.…”
Section: Two-stage Least Squaresmentioning
confidence: 99%
“…We are not the first to use these data. Biyase and Zwane (2015) use a dynamic panel data estimator to estimate the returns to education in South Africa from 2008-2012; they find that the returns to an additional year of education is approximately 47%. While there is increasing skepticism about the veracity of panel models that use lagged dependent variables as instruments, we use Biyase and Zwane as a benchmark to which we compare our estimated returns to education in various sub-populations of South Africa.…”
Section: Datamentioning
confidence: 99%